2020
DOI: 10.1200/jco.2020.38.15_suppl.9007
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II trial comparing the efficacy of standard-dose with high-dose twice-daily thoracic radiotherapy (TRT) in limited disease small-cell lung cancer (LD SCLC).

Abstract: 9007 Background: Concurrent chemoradiotherapy is the standard treatment of LD SCLC. Some patients are cured, but most relapse and better treatment is needed. 45 Gy in 30 fractions BID is the most recommended TRT-schedule. Studies suggest that a higher TRT-dose might prolong survival, but hitherto, this has not been confirmed in randomized trials. We aimed to investigate whether high-dose BID TRT of 60 Gy in 40 fractions was feasible, tolerated, and improved survival. Methods: Patients > 18 years, performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A recent phase II study comparing 45 to 60 Gy BD was reported at ASCO and ESMO 2020 in abstract form only. It showed an improvement in 2-year survival but it should be noted that this study is unpublished and included 170 patients (22). These results cannot therefore be considered practice changing and will require confirmation in a phase III study.…”
Section: Dose and Fractionationmentioning
confidence: 87%
“…A recent phase II study comparing 45 to 60 Gy BD was reported at ASCO and ESMO 2020 in abstract form only. It showed an improvement in 2-year survival but it should be noted that this study is unpublished and included 170 patients (22). These results cannot therefore be considered practice changing and will require confirmation in a phase III study.…”
Section: Dose and Fractionationmentioning
confidence: 87%
“…In addition, when the ENR was applied, only 11.3% (34/300) of patients had locoregional in-field failure. A randomized trial reported by the ASCO in 2020 compared the efficacy of a radiation dose of 45 Gy in 30 f BID with 60 Gy in 40 f BID TRT in patients with LS-SCLC and revealed that patients who received a dose of 60 Gy BID had a statistically significant benefit in 2-year survival and MST compared to patients who received a dose of 45 Gy BID 27 . Although the radiation modalities used in this study may be the most recommended TRT-schedule for LS-SCLC at present, only the 2-year survival of patients was evaluated and long-term survival remains to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several phase III trials have reported better survival outcomes in patients with ES-SCLC when combining carboplatin-etoposide with atezolizumab[ 48 ] or durvalumab[ 49 , 50 ]. The results of two RCTs comparing dose escalation with the normofractionated scheme vs the “Turrisi” scheme are pending: CALGB 30610 (normofractionation to 70 Gy) and a Norwegian study involving high-dose (60 Gy) AHF-RT in the experimental arm[ 51 ].…”
Section: Introductionmentioning
confidence: 99%